A Study for Exploring Information Literacy of PhD Student - Arniati Arniati (Pusat P2M Politeknik Negeri Batam, 2017)
The search process research topic is concerned for every doctoral student from all major colleges and all educational subjects. Previous studies indicate that the information literacy is a tool aids in the process of finding a research topic. This study aims to determine how the role of information literacy for doctoral students to find a thesis topic through interviews with doctoral students of engineering and non-engineering majors from several countries. The results showed that the use of information literacy required in the process of finding a research topic by using the channel information journal in websites and search engines is the most frequently used by students. Information literacy education in the form of short courses on material which is supporting the conduct of research, guides and self-learning module is a new discovery in this research.